2017
DOI: 10.1002/polb.24563
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the localization of finely dispersed cellulose nanocrystal in poly (lactic acid)/bio‐polyamide11 blends

Abstract: A versatile approach to control the localization of cellulose nanocrystal (CNC) in PLA/PA11 blends is presented. A PEO/CNC mixture with a high level of CNC dispersion is prepared through a combination of high pressure homogenization and freeze-drying. The prepared PEO/CNC mixture is then incorporated into the PLA/PA11 blends using two different strategies. Typically for CNC/PLA/PA11, the CNCs selectively localize in PA11. However, PEO-coated CNC particles segregate into PLA irrespective of whether the PEO/CNC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…To better localize the CNCs after melt mixing, SEM and AFM analyses were done at higher magnification and SEM and AFM phase images of aPLA/PBAT and scPLA/PBAT blend nanocomposites are presented in Figure 7 a–j, respectively. As reported elsewhere [ 40 , 41 ], the CNCs particles appear as white dots (arrows) and also rods (circles) in these images. The cellulose nanocrystals in the aPLA/PBAT blend nanocomposites have migrated from the PLA phase, when CNCs were initially added to aPLA ( Figure 7 a,d) or both phases ( Figure 7 c,e), to the surface of the PBAT droplets (circles and arrows).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…To better localize the CNCs after melt mixing, SEM and AFM analyses were done at higher magnification and SEM and AFM phase images of aPLA/PBAT and scPLA/PBAT blend nanocomposites are presented in Figure 7 a–j, respectively. As reported elsewhere [ 40 , 41 ], the CNCs particles appear as white dots (arrows) and also rods (circles) in these images. The cellulose nanocrystals in the aPLA/PBAT blend nanocomposites have migrated from the PLA phase, when CNCs were initially added to aPLA ( Figure 7 a,d) or both phases ( Figure 7 c,e), to the surface of the PBAT droplets (circles and arrows).…”
Section: Resultssupporting
confidence: 82%
“…They showed that irrespective of the preparing method the spray dried CNCs preferred to remain in the PA11 phase, which was the thermodynamically favorable phase. Heshmati et al [ 41 ] also showed that using poly(ethylene oxide) (PEO) as a polymer carrier for CNCs in the blend of PLA/PA11 resulted in the localization of the CNCs in PLA, which was not the thermodynamically favorable phase for the CNCs.…”
Section: Introductionmentioning
confidence: 99%
“…PLA presents good mechanical properties such as high strength, high modulus and excellent transparency . But the brittleness and low thermal stability of PLA hinder its large‐scale commercial applications . To overcome these limitations and to enhance the toughness of PLA, extensive efforts have been made, and several methods have been introduced, such as chemical copolymerization, plasticization, blending and production of composites via incorporation of fillers .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 But the brittleness and low thermal stability of PLA hinder its large-scale commercial applications. 9,10 To overcome these limitations and to enhance the toughness of PLA, extensive efforts have been made, and several methods have been introduced, such as chemical copolymerization, 11 plasticization, 12 blending [13][14][15][16] and production of composites via incorporation of fillers. [17][18][19] Among these various modification techniques, blending of PLA with other polymers (especially flexible ones) is usually used as the most perfect, economic and efficient method for improving its toughness.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Incorporating CNCs as a reinforcing agent in PLA or PBAT could improve the mechanical and thermal properties of these biodegradable polymers throughout a wide temperature range, overcoming these disadvantages in PLA and PBAT. [13][14][15][16] While melt mixing leads to agglomeration of CNCs as a result of strong inter-particle interactions, [17][18][19][20] approaches such as in-situ polymerization, [21][22][23] compatibilization, and chemical modifications [24][25][26][27] can be costly and cumbersome. Therefore, solution casting has been considered as an efficient method for dispersion and distribution of CNCs in the laboratory, but the method is still of limited practice by the industry due to use of expensive and toxic solvents.…”
Section: Introductionmentioning
confidence: 99%